Size effects in the magnetization of a superconducting wire - Venegas, Pablo Antonio [UNESP] (AIP Publishing, 1999)
The size effects in the magnetization of a long cylindrical wire of circular cross section in the presence of an external magnetic field are investigated. For this study the London theory is used with boundary conditions appropriate for this geometry. Using the Monte Carlo simulated annealing method, the free energy of the mixed state is minimized with respect to the vortex positions. The ground state of the vortex lattice for n = 1 up to 18 vortices for a given radius of the cylinder is obtained. It is found that the finite size of the sample provokes a matching effect in the magnetization, as found in experiments with superconducting samples of finite size but different geometry. © 1999 American Institute of Physics.